Skull base reconstruction using in situ bone flap in patients with pituitary adenomas treated by endoscopic endonasal approach - Chen, Kaile; Dai, Kexiang; Liu, Zhiyuan; Liu, Jinlai; Yu, Kuo; Lu, Ailin; Zhao, Peng (Frontiers in Neurology, 2023)
Objective: To study the effect of in situ bone flap (ISBF) repositioning, a recently proposed rigid skull base reconstruction technique, on patients diagnosed with pituitary adenoma undergoing endoscopic endonasal approach (EEA). Method: A retrospective analysis was conducted of 188 patients with pituitary adenomas who underwent EEA from February 2018 to September 2022. Patients were divided into the ISBF group and non-ISBF group, according to whether ISBF was used during skull base reconstruction. Results: Of the 75 patients in the non-ISBF group, 6 had postoperative cerebrospinal fluid (CSF) leakage (8%), while only 1 of 113 patients in the ISBF group (0.8%), had postoperative CSF leakage, indicating that the incidence of postoperative CSF leakage in the ISBF group was significantly lower than that in the non-ISBF group (P=0.033). In addition, we also found that the postoperative hospitalization days of patients in the ISBF group (5.34±1.24) were significantly less than those in the non-ISBF group(6.83±1.91, P=0.015). Conclusion: ISBF repositioning is a safe, effective, and convenient rigid skull base reconstruction method for patients with pituitary adenoma treated by EEA, which can significantly reduce the rate of postoperative CSF leakage and shorten postoperative hospital stays.